Study of clinical profile of childhood extra pulmonary tuberculosis - Gosai, Dhara K.; Gosai, Jigar B.; Shukla, Omprakash S. (International Journal of Research in Medical Sciences, 2017)
Background: Tuberculosis is the second most common cause of death from infectious disease at the global level, being second only to AIDS. Good data on the burden of all forms of TB amongst children in India is not available; most surveys conducted have focused on pulmonary TB. The present study was designed to study clinical profile of various forms of childhood EPTB. Objective of current study was to study clinico-epidemiological profile of various forms of childhood EPTB. Methods: Retrospective analysis of clinical profile of 100 patients of childhood EPTB in the age group of 6 months to 12 years. Results: Age distribution in our study showed that 62% cases falling in the age 0-5 years and 38% cases in 5-12 years (P = 0.041) with male to female ratio of 1.9:1. 96% (P = 0.016) of the patients belonged to the lower socio-economic class (P = 0.01). The distribution of EPTB was - TBME (46%), disseminated TB (21%), pleural effusion (12%), abdominal TB (10%), TB lymphadenitis (7%), Osteoarticular (4%). 28% of the patients had mild to moderate malnutrition (PEM Grade-I,II) and 46% (PEM Grade-III,IV) were severely malnourished. 66% of the patient were BCG vaccinated & history of Koch’s contact were present in 28% of the all cases. In CNS tuberculosis, fever was present in 97% followed by altered sensorium & convulsion in 80%, tonic posturing in 60% & abnormal movements in 4% and in most common sign was tonic posturing in 60%, crack pot sign positive in 41%. In abdominal tuberculosis - fever (100%), anorexia (90%), weight loss (80%) abdominal pain (50%) & hepatomegaly was common finding seen in 100% of abdominal tuberculosis. Conclusion: Childhood EPTB is commonly seen in children age more than 1 year, lower socioeconomic class & in severely malnourished. CNS tuberculosis commonly present with fever, altered sensorium, convulsion, abnormal movements while abdominal TB present with fever, anorexia, weight loss & abdominal pain.